SOSIALISASI DAN PELATIHAN PENDIDIKAN KARAKTER BAGI ANAK DAN REMAJA JEMAAT GPI DIASPORA KOTA SORONG - Adolfina Putnarubun; Ferdinando Solissa; Lanny Wattimena (Nusantara Hasana Journal, 2022)
The growth and development of children is also strongly influenced by the environment in which the child is located, whether with friends he hangs out with, the environment in which he lives or the school environment. Seeing from the various environmental opportunities that can slowly help shape the character of children, it is very important that there is a continuous effort in fostering and training children and adolescents to think and act positively. Bad associations destroy good habits (1 Cor 15:33), this part of the verse of God's Word reminds us that the good and bad character of a person depends on who the person associates with. The development of science, especially in technology, is very much felt in this modern era. To respond to this issue, this socialization and training is carried out as a form of our collective concern in building the nation's character through early development for children and youth in the environment, the city where we live. This character building is carried out with the aim of equipping children in undergoing their growth and development period, as well as encouraging children to have a mature self-concept and have a filter in their future interactions. Ready to be a Leader and Maintain Association, are two material topics that are packaged to later become provisions for children and adolescents, especially the participants of this service activity, namely children and youth of the GPI Diaspora Congregation in Sorong City.